Estimates of Ad Valorem Equivalents of Barriers Against Foreign Suppliers of Services in Eleven Services Sectors and 103 Countries - Jafari, Yaghoob (World Bank Group, Washington, DC, 2014)
A new database on the barriers faced by foreign suppliers of services has been produced by the World Bank. Data for 103 countries are available on 11 of the most important services sectors in international trade. Based on these data and building on the methodology and publications supported by the Australian Productivity Commission, this paper produces estimates of the ad valorem equivalents of the barriers for all these sectors and countries. Compared with estimates available in the literature that are based on assessments of country- and sector-specific barriers to services providers, the estimates expand the set of sectors and more than triple the set of countries for which estimates of the ad valorem equivalents of the services barriers are available.